2013
DOI: 10.32800/abc.2013.36.0209
|View full text |Cite
|
Sign up to set email alerts
|

Pets becoming established in the wild: free–living Vietnamese potbellied pigs in Spain

Abstract: Vietnamese potbellied (VPB) pigs (Sus scrofa) are a common pet in North America and Europe, but their recent decrease in popularity has increased their abandonment. Our main aim was to identify potential cases of free–living VPB pigs in Spain through an in–depth Google search. We identified 42 cases of free–living VPB pigs distributed throughout the country. The number of free–living VPB pigs reported increased by year but the species abundance still seems to be low. Signs of VPB pig reproduction and possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…This study evidences the presence of pet pigs stablished in the wild due to deliberate or accidental abandonment, resulting in establishments in new colonies(Delibes-Mateos & Delibes, 2013). The presence of pregnant females, piglets and hybrids in the study demonstrated the hybridization between miniature pigs and wild boars in Catalonia, since animals of different age, sex and species were found coexisting but not being castrated.TA B L E 2Note: A, forest; B, outdoor cement; C, outdoor enclosure.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…This study evidences the presence of pet pigs stablished in the wild due to deliberate or accidental abandonment, resulting in establishments in new colonies(Delibes-Mateos & Delibes, 2013). The presence of pregnant females, piglets and hybrids in the study demonstrated the hybridization between miniature pigs and wild boars in Catalonia, since animals of different age, sex and species were found coexisting but not being castrated.TA B L E 2Note: A, forest; B, outdoor cement; C, outdoor enclosure.…”
supporting
confidence: 57%
“…This study included 211 miniature pigs of different ages and sexes from a North‐East region of Spain (Catalonia) during December 2018 to January 2020. Thirty animals out of two hundred and eleven were hybrids between miniature pig and wild boar according to morphological characteristics (Delibes–Mateos & Delibes, 2013 ). Hybrids may show characteristics of both animals as a more compact body and longer legs, longer hair or even absence thereof, long snout or also appearance of animals with flat snout (Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adult animals possess a pot-belly shape with droopy back posture. Among different pig breeds, Vietnamese pot-bellied pigs (Sus scrofa) have pot-belly shape abdomen [2] . The male Zovawk animals are heavier till one year of age (30-35 Kg) and at around three years of age females (50-60 Kg) are usually heavier than the males (45-50 Kg) (Figure 1).…”
Section: Physical Characteristicsmentioning
confidence: 99%
“…In addition, we received many reports of pot-bellied pigs and in some cases, these animals had spent several seasons outside of captivity, suggesting that these abandoned pets are capable of surviving in the wild in Ontario. Pot-bellied pigs contribute to the wild pig population in other jurisdictions as well (e.g.,Caudell et al, 2013;Delibes-Mateos & Delibes, 2013).…”
mentioning
confidence: 98%